Associations Between Temperament and DSM-IV Externalizing Disorders in Children and Adolescents - RETTEW, DAVID C. (2004)
This study investigated associations between child temperament and DSM-IV disorders in children. A total of 156 probands (97 boys, 59 girls; mean age = 10.78 years) and 154 randomly selected siblings were assessed using the Junior Temperament and Character Inventory (JTCI) and a structured DSM-IV interview. Subjects were placed in nonoverlapping groups of (1) attention-deficit hyperactivity disorder (ADHD) only, (2) disruptive behavior disorders (DBD) only, (3) DBD plus an affective and/or anxiety disorder (DBD+Int), and (4) controls with no diagnosis. Many JTCI scales were found to differ between diagnostic groups and controls. Regression analyses showed independent associations between low persistence and ADHD-only group membership, high novelty seeking (NS), and the DBD-only group and between high harm avoidance (HA) and DBD+Int group membership. The interaction NS × HA was related to the ADHD-only group. Future research is needed to determine the mechanism of these association.